Pharmacological targeting of the mitochondrial phosphatase PTPMT1 sensitizes hepatocellular carcinoma to ferroptosis - Miaomiao Li; Yi Wang; Xinyan Li; Jiayi Xu; Liangwen Yan; Shenkang Tang; Chenyue Liu; Mengjiao Shi; Rongrong Liu; Yaping Zhao; Yi Zhang; Lan Yang; et al. (Cell Death and Disease)
Abstract Protein tyrosine phosphatase mitochondrial 1 (PTPMT1), is a member of the protein tyrosine phosphatase superfamily localized on the mitochondrial inner membrane, and regulates the biosynthesis of cardiolipin. Given the important position of PTPMT1 in mitochondrial function and metabolism, pharmacological targeting of PTPMT1 is considered a promising manner in disease treatments. In this study, we mainly investigated the role of PTPMT1 in hepatocellular carcinoma (HCC) ferroptosis, a new type of cell death accompanied by significant iron accumulation and lipid peroxidation. Herein, the pharmacological inhibition of PTPMT1 was induced by alexidine dihydrochloride (AD, a dibiguanide compound). Human HCC cell lines with PTPMT1 knockout and PTPMT1 overexpression were established using CRISPR/Cas9 and lentiviral transduction methods, respectively. The position of PTPMT1 in regulating HCC ferroptosis was evaluated in vitro and in vivo. Our results indicated that pharmacological inhibition of PTPMT1, facilitated by AD treatment, heightens the susceptibility of HCC to cystine deprivation-ferroptosis, and AD treatment promoted the conversion from ferritin-bound Fe3+ to free Fe2+, which contributed to the labile iron pool in cytoplasm. Meanwhile, pharmacological inhibition of PTPMT1 also induced the formation of both swollen mitochondria and donut mitochondria, and enhanced the metabolism process form succinate to fumarate in mitochondrial tricarboxylic acid (TCA) cycle, which increased the sensitivity of HCC cells to cystine deprivation-induced ferroptosis. In total, our work reveals the close association of PTPMT1 with cysteine deprivation-induced ferroptosis, providing a novel insight into chemotherapy strategies against human HCC.